Elie Wiesel's fictional universe : the paradox of the mute narrator - Berman, Mona (Rhodes University, Faculty of Humanities, Department of Literary Studies in English, 1986)
The approach I have chosen for my study is to analyse the narrative techniques in Wiesel's fiction, with particular emphasis on the role of the narrator and listener in the narratives. This will not only highlight aspects of his authorial strategy involving the reader's response to various dimensions of the Holocaust, but will allow an appraisal of the literary merit of Wiesel's novels. The hushed reverence that tends to accompany allusions to Auschwitz and its literature has impeded certain theoretical investigations, with the result that most critical studies undertaken on Wiesel's works have dealt predominantly with themes and content rather than with form. A narrative approach, however, while it accounts for themes, does so within the narrative process of the work. Form and content are examined as interwoven entities in the particular context of an individual work. My decision to adopt this pursuit is based on the conviction that Wiesel's fiction is a significant contribution to the literature of testimony, not only because of its subject matter, but also because of the way in which his narrators unfold their stories with words suspended by silence in the text. The paradox of the mute narrator, the title of my study, is intended to convey the paradoxical quality of Wiesel's fiction and to show how silence, which is manifested in the themes of his work, is concretized by his strategy of entrusting the transmission of the tale to narrators, who, for various reasons have been silenced. A mute by definition cannot emit an articulate sound. A narrator, on the other hand, is a storyteller who is reliant on verbal articulation for communication. This contradiction in terms is dramatized in the novels and is symptomatic of the dilemma of Wiesel's narrators who are compelled to bear testimony through their silence. In my study of Wiesel's fiction, I will follow the chronological sequence in which the novels were written, although I will not be using a developmental approach, except to point out that the trilogy which marks the beginning of his exploration into narrative strategies, and The Testament, the last book I will be dealing with, are a culmination of his previous fictional techniques. While a developmental analysis of his fiction, particularly from a thematic point of view, enables the reader to gain insight into his background, which is important in a comprehensive study of his works, I feel that this avenue of investigation has been competently dealt with by other critics. Ellen Fine's Legacy of Night, one of the first book-length studies of Wiesel, puts forward a convincing argument for examining his fiction in chronological sequence as a kind of serialized journey from being a witness in l'univers concentrationnaire to bearing - witness in a post-Holocaust world. Furthermore, it is possible to trace the direction Wiesel's fiction follows, as in each book the seeds are sown for new ideas which are expanded upon in subsequent books. My discussion, however, will deal with the narrative process of each novel as an individual work in its own particular context. Apart from the trilogy which is examined in one chapter, and The Testament which serves as a conclusion to the study, I have not used cross references to Wiesel's other fiction when analysing specific books. Moreover, I have deliberately avoided including Wiesel's comments on his works and references to them in his essays, interviews and non-fiction writing. The reason for this approach is that I consider each novel to be a separate narrative work which merits an interpretative response that is independent of the comparative criteria that has up to now influenced the assessment of his fiction. (Introduction, p. 12-14)
Keywords: Wiesel, Elie, 1928- -- Criticism and interpretation; Holocaust, Jewish (1939-1945) -- Personal narratives; Auschwitz; Narration; Silence; English literature; Criticism